2005
DOI: 10.1111/j.1464-410x.2005.05563.x
|View full text |Cite
|
Sign up to set email alerts
|

Robot‐assisted vs pure laparoscopic radical prostatectomy: are there any differences?

Abstract: collating intraoperative data and early functional outcome. RESULTSThe mean surgical time for LRP and RAP was 235 and 202 min ( P > 0.05) and mean (95% confidence interval) blood loss 299 (40) and 206 (63) mL ( P = 0.014), with no transfusions in either group. The positive margin rate did not differ significantly (14% LRP and 12% RAP) and there was no biochemical recurrence in either group. Early functional outcomes were similar. CONCLUSIONSBoth LRP and RAP are technically demanding, but feasible, with the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
2
13

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(97 citation statements)
references
References 17 publications
5
75
2
13
Order By: Relevance
“…Initial outcomes of earlier RALP series have shown the feasibility of the procedure [8,9,11,13]. Some studies comparing pure LRP and RALP have also been published and showed interesting results after RALP [5,16,17]. Moreover, the use of a robotic system reduces the difficulty of complex laparoscopic techniques and seems to decrease markedly the learning curve compared with pure LRP.…”
Section: Discussionmentioning
confidence: 96%
“…Initial outcomes of earlier RALP series have shown the feasibility of the procedure [8,9,11,13]. Some studies comparing pure LRP and RALP have also been published and showed interesting results after RALP [5,16,17]. Moreover, the use of a robotic system reduces the difficulty of complex laparoscopic techniques and seems to decrease markedly the learning curve compared with pure LRP.…”
Section: Discussionmentioning
confidence: 96%
“…Regarding the comparison between RARP and LRP, Joseph and associates 74 conducted a single retrospective study that compared noncontemporary series of patients who were evaluated for erectile function recovery after LRP and RARP. At 3 months after surgery, only a nonstatistically significant trend in favor of RARP was observed.…”
Section: Potency Outcomesmentioning
confidence: 99%
“…After the introduction of serum prostate specific antigen (PSA) into the clinical screening strategy for prostate cancer, the stage at pathologic confirmation has decreased. As a result, most of the diseases discovered have been localized cancers (1). For these localized tumors, radical prostatectomy (RP) is the standard established treatment option, and the goals of RP in this stage are cancer cure, minimization of complications and perioperative suffering, and preservation of urinary continence and erectile function (2).…”
Section: Introductionmentioning
confidence: 99%